Efeito Aharonov-Bohm óptico em homobicamadas rotacionadas de MoS2 - Oliveira, André Pelais (2025)
With the advancement of exfoliation techniques for lamellar crystals, the experimental observation of intrinsically quantum physical phenomena in atomically flat materials has become accessible. Among these materials, Group VI transition metal dichalcogenides (TMDs), such as molybdenum disulfide (MoS2), stand out. In its semiconducting form, MoS2 exhibits notable optical properties, such as the intensification of photoluminescence when exfoliated into monolayers due to quantum confinement. By stacking two MoS2 monolayers with rotation angles close to 60°, a moiré superlattice is formed, which allows for the confinement of electrons and holes in different domains. Therefore, these rotated MoS2 bilayers (TBM) with H-type stacking represent a promising platform for the investigation of quantum technologies. The formation of moiré excitons, where electrons and holes are spatially separated and strongly correlated, combined with the application of magnetic fields, creates a physical system of interest. This particular configuration reveals physical phenomena that are still little explored in rotated TMDs. In this work, we report evidence of the optical observation of the Aharonov-Bohm effect in MoS2 TBMs. This quantum interference phenomenon manifests itself through oscillations of the photoluminescence intensity with well-defined periods as a function of the applied magnetic field. Additionally, inversion effects were observed in the polarization of biexcitons in relation to excitonic emission, reducing its intensity by 100%. The results of this work open pathways for the study of new physical properties of superlattices and for the investigation of quantum memory devices and moiré emitters.